Law Enforcement of Fisheries Crimes of Justice - Bahtiat Bahtiar (Indonesia Prime, 2020)
The essence of law enforcement of fisheries crime that is just can be achieved if law enforcement officials always strive to uphold the rule of law, uphold professionalism, integrity, morality and respect the rights and obligations of everyone. Determination of suspects against the perpetrators of IUU Fishing is not only for the skipper and the head of the engine room but also the ship owner and corporate management as well as the indictment of the public prosecutor and the verdict of the panel of judges is not too light (low). The results showed that to improve the coordination system, it is better to establish a joint office with One Stop Services (OSS) and use the latest and sophisticated radar in the form of Over The Horizon (OTH) to detect all types of ships operating at sea and the Geoogle Monitoring System (GMS) and for supervise the movement of ships at sea. The results showed that it is necessary to make improvements related to the legal system which includes legal substance, legal structure and legal culture.